Study the mechanical properties of lightweight concrete slab using polystyrene - Wan Ahmad Hamidi, Wan Mohd Abd Kalam (2016)
Nowadays, polystyrene was widely used as food and manufacturing production equipment as packaging tools to absorb vibration during handling and transportation process. It is estimated that it produced large amount of wastes as it abundantly used in the market. Due to its lightweight characteristics, it has potential to serve as aggregates replacement of coarse aggregates. Thus, a study of concrete made of polystyrene beads as aggregates was carried out. Through this study, the mechanical properties of polystyrene can be determined whether it is good or not when replace it as aggregate in the concrete. The main objective of this study is to determine the mechanical properties of the lightweight concrete slab using polystyrene. Several tests were conducted to determine the compressive strength, flexural strength, deformation and also crack pattern of the slabs. There were nine samples of slabs were constructed which consist of three different ratio,1:3:0(Control) ,1:2:1 and 1:1.75:1.25.Each ratio consists of three samples. All the samples were concreted and tested at Heavy Structure Laboratory Universiti Malaysia Pahang (UMP). From the compression test, the strength of the two ratio were lower than strength of the control. That is mean it meet the required characteristic of the study. The average load of control sample is the highest which is 81.84kN.Meanwhile the average load for ratio 1 and ratio 2 were 52.19kN and 51.59kN, respectively. For the deflection, the control sample also got the highest value which is 6.60mm. While ratio 1 and ratio 2 were 3.10mm and 1.90mm, respectively. The load and deflection are decrease due to the increasing amount of polystyrene. Besides, the type of crack and failure such as shear failure, compression failure and also tension failure also determined in this study. In a nutshell, polystyrene beads(EPS) can be used as aggregate replacement in the concrete. Overall of the study showed that the mechanical properties of lightweight concrete mainly influenced by the content of polystyrene beads and the strength decrease with the increase of the polystyrene content.